PENGARUH TERAPI BERMAIN TERHADAP KECEMASAN ANAK YANG MENJALANI KEMOTERAPI - Ningsih, Eka Wahyu (Coping: Community of Publishing in Nursing, 2015)
Cancer is one of the biggest killer diseases in the world. Cancer not only affects adults but children can also be at risk for cancer. Latest cancer treatment for children includes a combination of chemotherapy, radiation and sometimes surgery. Such actions require a very long time and often cause discomfort, side effects and lead to psychological problems. Children who undergo chemotherapy also showed psychological problems such as anxiety and psychosocial distress. One of the ways to minimize anxiety is to be given a child play therapy. Play therapy is a natural way to express the self conflict that not realized by the child himself and the best way to deal with anger, fear and grief. The purpose of this study was to determine the effect of play therapy on anxiety among children undergoing chemotherapy in Pudak Ward of General Public Hospital Sanglah Denpasar. This research is a pre-experimental research design with one group pre-test and post-test design. Sample consisted of 20 pediatric cancer patients were selected by purposive sampling, administered questionnaires to measure anxiety RCMAS anxiety then given play therapy. Based on the paired t-test results, obtained significant value (p) = 0.000 which is smaller than ? = 0.05 (5%). It can be concluded that there is effect of play therapy on children’s anxiety who undergo chemotherapy in Pudak Ward of General Public Hospital Sanglah Denpasar.
Keywords: cancer patients; chemotherapy; anxiety; play therapy